GOOD CORPORATE GOVERNANCE DI RUMAH SAKIT A DAN B - Firman Pribadi; Erwin Santosa; Bobet Evih Hedi Ihnuna Rusep (Universitas Muhammadiyah Yogyakarta, 2012)
This exploratif qualitative research is a longitudinal case study to see hospital A and hospital B good corporate governance (GCG) with Center for Good Corporate Governance (CGCG) Gajah Mada University (GMU) version of GCG questionnaires then completed by interview. Good corporate governance be observed by transparency, accountability & responsibility, responsiveness, and fairness principle intended for board of commissioners (board of supervisors), board of directors, executive office (manager), auditor, and stakeholders of the hospital. Result show that both of hospitals are at bad level of good corporate governance application, different scoring result both of their good corporate governance principles can be caused by local wisdom, organization behaviour, and organization culture factors.